Предмет: Математика, автор: alexandremiguel87

(X-1)dy-(y^2-6y)dx=0

Ответы

Автор ответа: Ilyazov45
0

(x-1)dy-(y^2-6y)dx=0;

\frac{dy}{(y^2-6y)}-\frac{dx}{x-1}=0;

\frac{dy}{y^2-6y} =\frac{dx}{x-1}

\int\frac{dy}{y^2-6y} =\int\frac{dx}{x-1} ;

1) \int\frac{dy}{y^2-6y}=\left \{ {{\frac{A}{y}+\frac{B}{y-6}=\frac{1}{y(y-6)}   } \atop {A(y-6)+By=1}}\atop{B=\frac{1}{6} };A=-\frac{1}{6}  \right.   \int\frac{dy}{y^2-6y}=\int-\frac{1}{6y}+\frac{1}{6(y-6)}dy=\frac{1}{6}\int\frac{1}{y-6}-\frac{1}{6}\int\frac{1}{y}=  \frac{1}{6}ln|y-6|-\frac{1}{6}ln|y|=\frac{1}{6}ln|\frac{y-6}{y} |+C

2) \int\frac{dx}{x-1}=ln|x-1|+C

\frac{1}{6}ln|\frac{y-6}{y} |=ln|x-1|+C

ln|\frac{y-6}{y} |=6ln|xC-C|;

\frac{y-6}{y}=(xC-C)^{6};

y=\frac{6}{1-(xC-C)^6}

\boxed{y=\frac{6}{1-C(x-1)^6} }

Похожие вопросы